Synthesis and Characterization of Niobium and Tantalum Complexes with Bidentate Ligand and its use in Ring Opening Polymerization of e-Caprolactone - Al-Khafaji, Yahya F.; Al-Lami, Mohammed R.; Abbas, Ahmed S.; Al-Ameri, Ameer; Albo Mousa, Ahmed Falah (Asian Journal of Chemistry, 2017)
Reaction of two equivalents of the bidentate 2,2'-PhCH[4,6-(t-Bu)2C6H2OH]2 with one equivalent of niobium pentachloride gave the complex Nb{2,2'-PhCH[4,6-(t-Bu)2C6H2O]2}2 (1) . Similar use of two equivalents of the same ligand with one equivalents tantalum pentachloride afforded Ta{2,2'-PhCH[4,6-(t-Bu)2C6H2O]2}2 (2). The molecular structure of complexes 1 and 2 have been characterized by IR and 1H NMR. Both complexes were investigated as catalysts for polymerization of cyclic esters (e-caprolactone) with no solvent at various time at 110 °C. In all cases the polymer produced was of high yield percent.